Single cell transcriptome in aneuploidies reveals mechanisms of gene dosage imbalance - Georgios Stamoulis (Nature Portfolio, 2019)
Gene dosage anomalies such as those caused by aneuploidy underlie diseases including Down syndrome. Here, the authors perform allele-specific single cell transcriptome analysis to investigate the mechanisms of gene dosage imbalance in fibroblasts with trisomies T21, T18, T13 and T8.